1997
DOI: 10.1101/gad.11.6.748
|View full text |Cite
|
Sign up to set email alerts
|

A novel Rap1p-interacting factor, Rif2p, cooperates with Rif1p to regulate telomere length in Saccharomyces cerevisiae.

Abstract: The Saccharomyces cerevisiae Rapl protein binds with high affinity to sites within the poly(Ci_3A) tracts at telomeres, where it plays a role in both telomere length regulation and the initiation of telomeric silencing. Raplp initiates silencing at telomeres by interacting through its carboxy-terminal domain with Sir3p and Sir4p, both of which are required for repression. This same domain of Raplp also negatively regulates telomere elongation, through an unknown mechanism. We have identified a new Rapl-interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
439
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 388 publications
(460 citation statements)
references
References 54 publications
18
439
2
Order By: Relevance
“…5A). Previously, it was found that Rif2 and Rif1 have synergistic effects in inhibiting telomerase (Wotton & Shore, 1997; Levy & Blackburn, 2004) and yet opposing effects in regulating the proliferation of telomere‐dysfunctional cdc13‐1 cells (Addinall et al ., 2008; Xue et al ., 2011). In conclusion, Rif1 is unique among many telomere‐associated proteins in facilitating proliferation of cells lacking telomeres, whereas Rif2 and Mre11 have the opposite effect to Rif1.…”
Section: Resultsmentioning
confidence: 99%
“…5A). Previously, it was found that Rif2 and Rif1 have synergistic effects in inhibiting telomerase (Wotton & Shore, 1997; Levy & Blackburn, 2004) and yet opposing effects in regulating the proliferation of telomere‐dysfunctional cdc13‐1 cells (Addinall et al ., 2008; Xue et al ., 2011). In conclusion, Rif1 is unique among many telomere‐associated proteins in facilitating proliferation of cells lacking telomeres, whereas Rif2 and Mre11 have the opposite effect to Rif1.…”
Section: Resultsmentioning
confidence: 99%
“…Deletion of either RIF1 or RIF2, which encode negative regulators of this pathway that interact directly with Rap1 (Hardy et al 1992;Wotton and Shore 1997), causes a telomere elongation phenotype that is considerably exacerbated by the presence of the pol12-216 mutation (Fig. 6C).…”
Section: Telomere Elongation In Pol12-216 Mutants Requires Telomerasementioning
confidence: 99%
“…Maintenance of telomere length about a fixed average value is achieved through a mechanism that appears to measure not the TG-repeat tract length per se, but, rather, the number of Rap1 proteins bound to it (Marcand et al 1997;Ray and Runge 1999a). The C terminus of Rap1 negatively regulates telomere elongation in cis (Kyrion et al 1992;Marcand et al 1996), a function that requires two additional proteins, Rif1 and Rif2, both of which interact physically with this domain of Rap1 (Hardy et al 1992;Moretti et al 1994;Wotton and Shore 1997). The inhibition of telomerase addition by Rap1-Rif1/2 complexes increases linearly as a function of telomere tract length (and presumably the number of Rap1-Rif1/2 complexes bound) through a mechanism that is at present unknown.…”
mentioning
confidence: 99%
“…Artificially targeting Rap1p to an individual telomere proportionately shortens the TG 1-3 tract in cis (25,26). This negative regulation requires Rif1p and Rif2p, proteins that bind to the C terminus of Rap1p and play overlapping, but not fully redundant, roles in telomere length homeostasis (13,19,41). The deletion of RIF1 or RIF2 increases the frequency of telomere elongation during a single cell cycle, suggesting that the Rap1p/ Rif1p/Rif2p complex modulates telomerase access in a manner responsive to telomere length (39).…”
mentioning
confidence: 99%